The Deployment Life Study Methodological Overview and Baseline Sample Description - Tanielian, Terri (RAND Corporation, 2014)
The Deployment Life Study was designed to provide a deeper understanding of military family readiness and its sources. This report describes the theoretical model that informed the study design, the content of the baseline assessment, the design and procedures associated with data collection, sampling and recruiting procedures, and the baseline sample of military families.